Search for novel proteins involved in the development of chemoresistance in colorectal cancer and fibrosarcoma cells in vitro using two-dimensional electrophoresis, mass spectrometry and microsequencing - Sinha-von Jaschke, Pranav; Schadendorf, Dirk (Electrophoresis, 1999)
In search of novel mechanisms that may lead to the development of chemoresistance of malignant tumors of the large bowel we used two-dimensional electrophoresis to identify proteins that were overexpressed in colorectal and fibrosarcoma cell lines that were resistant towards mitoxantrone. This cytostatic drug is known to lead to atypical multidrug resistance, i.e., the classical mechanism of multidrug resistance (MDR) accompanied by the overexpression of P-glycoprotein (P-gp) is ineffective. Using mass spectrometry and microsequencing we found adenine phosphoribosyl transferase and breast cancer specific gene 1 (BCSG1) overexpressed in the resistant colorectal tumor cell line. In the chemoresistant fibrosarcoma cell line we found two proteins that were overexpressed. One was identified as Rho-guanine dinucleotide phosphate (Rho-GDP) dissociation inhibitor and the other had sequence homologies with yeast protein yer-7. The putative role of these proteins is discussed.